ZAKAT DALAM PERSPEKTIF MAQASHID AL-SYARIAH - Aibak, Kutbuddin (Ahkam: Jurnal Hukum Islam, 2015)
Zakat as one of the pillars in Islam provides a alternative of socialprotection. Paying for zakat is not only a manifestation of worshippingAllah but also a social action to support for the improvement ofpeople’s life quality. Zakat is not a goal but it is a means to achievesocial justice and a means to reduce the number of poverty as well.Therefore, good management of zakat under the principles of syariahis a must.Kata kunci: Zakat, Pengeloaan Zakat, Maqashid al-Syariah